Pengaruh Daya Tarik Iklan Gojek Versi SebelumGojek Terhadap Keputusan Penggunaan Aplikasi - Ashri Lutfia; Jamiati KN (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Advertising is a type of communication in the form of visual, written or oral media. Advertisements make and encourage decisions to the viewing public that aim to attract consumers. Gojek is one of the companies that utilizes the YouTube platform as a place to attract consumers, one of which is their newest advertisement, namely "#BeforeGojek". The aim of this research is to find out what effect the Gojek advertisement version "#BeforeGojek" has on the decision to use the Gojek application among viewers of the Gojek YouTube advertisement (Survey of Communication Science Students, FISIP UMJ Class of 2020/2021). The theory used in this research is the Advertising Attractiveness theory which includes Meaningful (Impression), Believable (Trust), Distinctive (Characteristics) and uses the Purchasing Decision Process theory including Problem Recognition, Information Search, Alternative Evaluation, Purchase Decision, and Post-Evaluation Purchase. This research uses a quantitative approach with a survey method with a questionnaire as the data collection instrument. The data collection technique was carried out by distributing questionnaires given to 78 respondents to the 2020/2021 FISIP UMJ Communication Science Students. The questionnaire collection method used was random sampling. The results of the research show that the analysis indicates that the "#BeforeGojek" version of the Gojek advertisement had an impact on the decision to use the application by 55.8% and 44.2% was caused by factors outside the research. In the hypothesis test, it produces tcount (9.805) > ttable (1.665), so H0 is rejected and H1 is accepted, which means that there is an influence between the influence of the attractiveness of the "#BeforeGojek" version of Gojek advertising on the decision to use the application.